Review of the genus Chinoperla Zwick, 1980 (Plecoptera: Perlidae: Perlinae) from China - Mo, Rao-Rao; Liu, Rui-Jun; Wang, Guo-Quan; Li, Wei-Hai; Murányi, Dávid (European Journal of Taxonomy, 2021)
The Chinese species of the genus Chinoperla Zwick, 1980 are reviewed. One species from Hainan is described as new to science: C. changjiangensis sp. nov. Chinoperla gorohovi Sivec & Stark, 2010 is reported from China for the first time, with a redescripion and color images of the male, and the first description of the female and egg. Chinoperla nigrifrons (Banks, 1939) is redescribed and illustrated, synonymy of C. furcomacula (Wu, 1973) is confirmed. Taxonomic relationships within the studied species are discussed. A provisional key to the six known species of Chinoperla for China is presented.